MANAJEMEN PERENCANAAN DAN PELAKSANAAN PENDIDIKAN ISLAM DI MADRASAH ALIYAH NEGERI (MAN) 2 KOTA TASIKMALAYA - Yusuf Anggia, Iqbal (Program Studi Pendidikan Agama Islam, 2024)
The purpose of this research is to obtain an overview and analyze the Management of Islamic Education Planning and Implementation in the learning process. The research method used in this qualitative approach is the case study method. A research method that aims to describe a particular situation or field in an analytical, systematic factual and thorough manner. The results of this study indicate that: 1) Islamic education planning in the learning process at MAN 2 Tasikmalaya City is as follows: a) Teachers make learning tools, b) Teachers set learning objectives, c) Teachers choose and develop teaching materials, d) Teachers choose appropriate teaching media, and e) Teachers choose and utilize learning resources. 2) The implementation of Islamic education in the learning process at MAN 2 Tasikmalaya City is as follows: a) Teachers create the right learning climate or atmosphere, b) Teachers observe learning activities, c) Teachers organize students in learning activities, d) Teachers choose and determine learning methods that are considered the most appropriate and effective, e) Teachers assess students' learning achievements, and f) Teachers carry out follow-up assessment results.